Ditch the Act Reveal the Surprising Power of the Real You for Greater Success. - Kim, Leonard; Foland, Ryan (McGraw-Hill, 2019)
Use your failure, mistakes, and vulnerabilities to fund success--the proven guide to building a powerful personal brand through the fearless admission of just being human. The authors explain why vulnerability is important and how it cultivates more durable connections than any polished persona can.